Implementation of Hidden Curriculum in The Subject of Islamic Religious Education and Character at SMK Negeri 57, Jakarta (Jakarta Public Vocational High School 57) - Suyanti, Eti; Suradika, Agus; Wahab, Muhbib Abdul; Masyitoh, Masyitoh; Bahri, Saiful (Technium Social Sciences Journal, 2023)
Purpose of this research is to find the following matters: (1) Implementation of the Hidden Curriculum in the subject of Islamic Religious Education and Character at SMK Negeri 57, Jakarta, (2) Supporting factors and inhibiting factors of the hidden curriculum in the subject of Islamic Religious Education and Character, (3) Evaluation of hidden curriculum in subject of Islamic Religious Education and Character, (4) Concept of implementation of hidden curriculum in the subject of Islamic Religious Education and Character in public schools. This research was conducted from June 2022 to March 2023, using qualitative research methods through a phenomenological approach. Data collection techniques were carried out using interviews, observation and documentation studies. Data analysis uses the interactive Miles and Hubberman model, namely data reduction, display and verification. The validity of the data is measured using source angulation techniques and extending the participation of researchers. The results of this research show that: (1) The implementation of the hidden curriculum in the subject of Islamic Religious Education and Character at SMK Negeri 57, Jakarta consists of aspects of habituation, coaching, assignments, worship, extracurriculars, various school development activities, instilling values, growing empathy, tolerance and collaboration. (2) the supporting factor for the hidden curriculum in the subject of Islamic Religious Education and Character at SMK Negeri 57, Jakarta is collaboration with stakeholders, while the inhibiting factor is the pandemic conditions for two years so that learning is carried out online. Therefore, there are no activities at school (3) Evaluation of the hidden curriculum in the subject of Islamic Religious Education and Character at SMK Negeri 57, Jakarta has not been carried out optimally. Habituation, assignments and role modeling were carried out again after the offline learning was implemented, so it was not implemented thoroughly. (4) Implementation of the Hidden Curriculum in the subject of Islamic Religious Education and Character in public schools, has the concept of (a) implementation is carried out in an integrated manner with school development through habituation, assignments and exemplary activities which cover various aspects in dealing with the lack of learning duration in the subject of Islamic Religious Education and Character in schools. (b) the more school development programs there are, the more dynamic the strengthening of students’ character, (c) example and habituation are the most effective strategies in implementing the hidden curriculum since the example set by educators forms the students to follow attitudes and behavior that shape character, while the habituation carried out will build good habits that will be carried over until the students become adults.